La valoración de los elementos de los costos predeterminados como herramienta de gestión financiera - Baculima Condoy, Priscilla Anabell (2015)
In industrial enterprises the systems default costs estimated to represent an attempt in the advance of the actual costs, however the companies don't give it the importance it deserves without knowing what the results are useful for decision-making or also opt for traditional cost systems that do not conform to the reality of their production costs by obtaining as a result unsound decisions for the company. The objective of this project is to implement the system default costs estimated a model that allows us to establish the estimate of each of the elements of costs, such as the; direct materials, direct labor, and indirect costs of manufacture; we will serve as a tool for financial management applied to an industrial enterprise. This work is carried out under the scientific methodology with quantitative approach that seeks relate the theoretical with the practical by highlighting the techniques of observation of its procedures within the organization and the strategic interviewing people within the company that allowed us to identify the lack of procedures in the estimate of the costs of production, all of the above reflects the importance of the estimate of the costs and subject the implementation of a model of default costs estimated.